Electrochemical synthesis of nanowire anodes from spent lithium ion batteries. (1st October 2019) - Schiavi, Pier Giorgio; Farina, Luca; Zanoni, Robertino; Altimari, Pietro; Cojocariu, Iulia; Rubino, Antonio; Navarra, Maria Assunta; Panero, Stefania; Pagnanelli, Francesca
Abstract: A novel process is proposed to produce nanostructured batteries anodes from spent lithium-ion batteries. The electrodic powder recovered by the mechanical treatment of spent batteries was leached and the dissolved metals were precipitated as cobalt carbonates. Two different precipitation routes were separately tested producing cobalt carbonates with different Cu and Fe contents. Nanowire anodes were produced by electrodeposition into nanoporous alumina templates from the electrolytic baths prepared by dissolution of the precipitated carbonates. The electrochemical performances of the produced anodes were evaluated as compared to nanowire anodes produced with the same electrodeposition method but using a synthetic cobalt bath. The application of the carbonates produced by directly precipitating all the leached metals gave nanowires with capacity about halved as compared to the nanowires electrodeposited from the synthetic bath. Selectively removing Cu and Fe prior cobalt carbonate precipitation yielded, in contrast, nanowires with capacity initially larger and then gradually approaching that attained by the nanowire electrodeposited from the synthetic bath. A detailed analysis is presented describing the role of metallic impurities in determining the capacity of the produced nanowires. The impact of the illustrated results for the development of sustainable recycling processes of lithium-ion batteries is discussed. Graphical abstract: Image 1